Epigenetic and post-transcriptional modulation of SOS1 can promote breast cancer metastasis through obesity-activated c-Met signaling in African American women - Xing, Fei (Cancer Res, 2021)
Ethnicity is considered to be one of the major risk factors in certain subtypes of breast cancer. However, the mechanism of this racial disparity remains poorly understood. Here we demonstrate that SOS1, a key regulator of Ras pathway, is highly expressed in African American (AA) breast cancer patients compared to Caucasian American (CA) patients. Because of the higher obesity rate in AA women, increased levels of SOS1 facilitated signal transduction of the c-Met pathway which was highly activated in AA breast cancer patients via HGF secreted from adipocytes. Elevated expression of SOS1 also enhanced cancer stemness through upregulation of PTTG1 and promoted M2 polarization of macrophages by CCL2 in metastatic sites. SOS1 was epigenetically regulated by a super-enhancer identified by H3K27ac in AA patients. Knockout of the super-enhancer by CRISPR in AA cell lines significantly reduced SOS1 expression. Furthermore, SOS1 was post-transcriptionally regulated by miR-483 whose expression is reduced in AA patients through histone tri-methylation (H3K27me3) on its promoter. The natural compound taxifolin suppressed signaling transduction of SOS1 by blocking the interaction between SOS1 and Grb2, suggesting a potential utility of this compound as a therapeutic agent for AA breast cancer patients.